Imaging of retinal and choroidal manifestations of gastrointestinal disease (2017)
Ocular manifestations of gastrointestinal diseases are uncommon. This chapter describes multimodal imaging of the most frequent gastrointestinal disorders, and associated retinal and choroidal findings. Inflammatory bowel disease, Whipple's disease, and Behçet's disease may have vaso-occlusive manifestations, as well as vasculitis, retinitis, and changes in the choroid, due to inflammation. Purtscher's like retinopathy associated with pancreatitis presents with changes associated to vaso-occlusive disease. Avitaminosis A has degenerative flecks in the retina that may be reversible with adequate supplementation. Familial adenomatous polyposis syndrome, also considered in this chapter, has typical clinical characteristic changes in the retinal pigment epithelium that help in the diagnosis. © Springer Nature Singapore Pte Ltd. 2018. All rights reserved.